2019
DOI: 10.1002/aenm.201900266
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Conducting Polymers to High Order: Toward Conductivities beyond 105 S cm−1 and Thermoelectric Power Factors of 2 mW m−1 K−2

Abstract: Here, an effective design strategy of polymer thermoelectric materials based on structural control in doped polymer semiconductors is presented. The strategy is illustrated for two archetypical polythiophenes, e.g., poly(2,5‐bis(3‐dodecyl‐2‐thienyl)thieno[3,2‐b]thiophene) (C12‐PBTTT) and regioregular poly(3‐hexylthiophene) (P3HT). FeCl3 doping of aligned films results in charge conductivities up to 2 × 105 S cm−1 and metallic‐like thermopowers similar to iodine‐doped polyacetylene. The films are almost optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
181
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(203 citation statements)
references
References 57 publications
14
181
0
Order By: Relevance
“…3,4 Sequential doping avoids possible complications that arise if the doped material is poorly soluble in the casting solvent and in some cases may allow for the preservation of some of the structural order present in the pristine semiconductor film. Although widely applied to the p-doping of P3HT [5][6][7][8] and PBTTT, 9,10 there are only few reports of the sequential n-doping of solution-processed polymers. 11 The air-stability of oxidants, hole-transport materials, and their doped combinations often allow for easy handling in air.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Sequential doping avoids possible complications that arise if the doped material is poorly soluble in the casting solvent and in some cases may allow for the preservation of some of the structural order present in the pristine semiconductor film. Although widely applied to the p-doping of P3HT [5][6][7][8] and PBTTT, 9,10 there are only few reports of the sequential n-doping of solution-processed polymers. 11 The air-stability of oxidants, hole-transport materials, and their doped combinations often allow for easy handling in air.…”
Section: Introductionmentioning
confidence: 99%
“…Highly conductive hole-transport materials are achievable in many polymer-dopant systems. 7,[12][13][14][15][16] In contrast, electrontransport materials and their n-doped derivatives lag behind p-type polymers in terms of both mobility and conductivity. [17][18][19] One reason is that the dopant-induced polaronic charge carriers tend to be localized on acceptor moieties, and the electronic coupling between adjacent acceptor sites is often poor.…”
Section: Introductionmentioning
confidence: 99%
“…72 Recent studies have demonstrated that the dopant molecules intercalate inside the crystal lattice of PSCs. [73][74][75] The key role of dopant intercalation and ordering on the structure and thermoelectric properties of PSCs has been highlighted. Important and fundamental aspects deal with the precise position and distribution of dopant molecules in the crystalline structure of the PSCs and how it controls the electronic properties of the doped systems.…”
Section: Discussionmentioning
confidence: 99%
“…On a more applied basis, crystallization and orientation of TE materials has emerged as a valuable and effective means to reach high TE power factors. [74][75][76] The know-how developed in monitoring the crystallization of PSCs is essential to further optimize the structure of the doped conducting systems. New strategies for the preparation of highly ordered conducting polymers must be developed.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] The development of both n‐type and p‐type efficient materials is then required to benefit from voltage summation. While high control over the organization of conjugated polymer chains allowed to achieve a metallic‐like electrical conductivity in p‐doped polymer films, [ 15,16 ] the development of n‐type polymers with efficient transport properties in their intrinsic and doped states remains a challenge. [ 17,18 ] To date, the highest electron mobility and thermoelectric performance for n‐type polymers were achieved for those composed of fluorinated derivatives of the electron‐deficient benzodifurandione‐based oligo( p ‐phenylene vinylene) (BDOPV) unit.…”
Section: Introductionmentioning
confidence: 99%